2010
DOI: 10.1016/j.jbiotec.2009.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Variant Cry1Ia toxins generated by DNA shuffling are active against sugarcane giant borer

Abstract: Sugarcane giant borer (Telchin licus licus) is a serious sugarcane pest in Americas whose endophytic lifestyle hampers effective chemical and biological controls. Therefore, development of alternative control methods is extremely important. Envisaging development of transgenic plants resistant to this pest, we investigated the effect of the Bacillus thuringiensis Cry protein Cry1Ia12synth (truncated protein lacking C-terminus with plant codon usage) and variants against T. l. licus. cry1Ia12synth gene was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 32 publications
(31 reference statements)
0
50
0
Order By: Relevance
“…Bioassay results indicated that the expressed proteins of Cry7Ca1 and the activated toxins (toxins 1 and 2) showed significant activity against 2nd instar locusts, and after 7 days of infection, the estimated 50% lethal concentrations (LC 50 s) were 8.98 g/ml for the expressed Cry7Ca1, 0.87 g/ml for the activated toxin 1, and 4.43 g/ml for the activated toxin 2. The ␦-endotoxin also induced histopathological changes in midgut epithelial cells of adult L. migratoria manilensis.Bacillus thuringiensis is a spore-forming entomopathogenic bacterium that produces parasporal crystals composed of proteins called ␦-endotoxins during sporulation (8,19,36,45). It is reported that B. thuringiensis exhibits specific activity against Lepidoptera, Diptera, Coleoptera, Homoptera, Hymenoptera, Mallophaga, nematodes, and other invertebrates (2,7,9,24,44).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bioassay results indicated that the expressed proteins of Cry7Ca1 and the activated toxins (toxins 1 and 2) showed significant activity against 2nd instar locusts, and after 7 days of infection, the estimated 50% lethal concentrations (LC 50 s) were 8.98 g/ml for the expressed Cry7Ca1, 0.87 g/ml for the activated toxin 1, and 4.43 g/ml for the activated toxin 2. The ␦-endotoxin also induced histopathological changes in midgut epithelial cells of adult L. migratoria manilensis.Bacillus thuringiensis is a spore-forming entomopathogenic bacterium that produces parasporal crystals composed of proteins called ␦-endotoxins during sporulation (8,19,36,45). It is reported that B. thuringiensis exhibits specific activity against Lepidoptera, Diptera, Coleoptera, Homoptera, Hymenoptera, Mallophaga, nematodes, and other invertebrates (2,7,9,24,44).…”
mentioning
confidence: 99%
“…Bacillus thuringiensis is a spore-forming entomopathogenic bacterium that produces parasporal crystals composed of proteins called ␦-endotoxins during sporulation (8,19,36,45). It is reported that B. thuringiensis exhibits specific activity against Lepidoptera, Diptera, Coleoptera, Homoptera, Hymenoptera, Mallophaga, nematodes, and other invertebrates (2,7,9,24,44).…”
mentioning
confidence: 99%
“…The evident consequence of this further domestication is the need to substitute general pesticides for new, more specific pesticides like Bt to counter plant pests. Several new plant toxic proteins with insecticidal properties have potential in this respect [129][130][131] some of which are commonly found in foods we already eat (e.g. [132]) and we know how to inactivate them.…”
Section: Discussionmentioning
confidence: 99%
“…In another example a triple mutation (N372A, A282G and L283S) in domain II loop of Cry1Ab resulted in a 36-fold increase in toxicity to Lymantria dispar and this correlated with an increased binding affinity of greater than 18-fold to brush border membrane vesicles which also resulted in higher toxin concentration at the binding site (Rajamohan et al 1996). Natural evolutionary trends have been used in analysing the divergence and host specificity in Cry toxins ) and biotechnological techniques like gene shuffling has been used in artificially directing the evolution of new genes with novel characteristics (Stemmer 1994a, b;Zhao and Arnold 1997;Lassner and Bedbrook 2001;Craveiro et al 2010). Craveiro et al used DNA shuffling technique to produce four variants of Cry11A12synth and Cry11A12 that, unlike the parent toxins, had toxicity against Telchin licus licus.…”
Section: Genetic Manipulation Of Existing Bt Strains and Itsmentioning
confidence: 99%